2023
DOI: 10.1021/acsomega.3c02813
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Photophysical, Electrochemical, and DFT Studies of Piperidyl and Pyrrolidinyl Chalcones

Abstract: Small organic molecules with interesting optical and electrochemical properties find applications as organic luminescent materials. In this work, we report the synthesis of novel chalcones with D−A−D and D−A−D−A architecture, followed by their optical, electrochemical, and computational studies. The absorption band of these compounds occurs at 360−480 nm with emission maxima appearing around 513−552 nm. The large Stokes shifts (Δλ) for all compounds (90−132 nm) suggest intramolecular charge transfer (ICT) in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…[29,30] The electrochemical properties of various chalcones have been demonstrated using a three-electrode cell system in the presence of anhydrous acetonitrile and tetrabutylammonium hexafluorophosphate electrolyte. [31][32][33] In addition, Slobodinyuk et al reported the electrochemical oxidation of series of asymmetric chalcones. [34] Kagatikar and co-workers assessed pyrene-based chalcones as functional materials applicable in organic electronics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[29,30] The electrochemical properties of various chalcones have been demonstrated using a three-electrode cell system in the presence of anhydrous acetonitrile and tetrabutylammonium hexafluorophosphate electrolyte. [31][32][33] In addition, Slobodinyuk et al reported the electrochemical oxidation of series of asymmetric chalcones. [34] Kagatikar and co-workers assessed pyrene-based chalcones as functional materials applicable in organic electronics.…”
Section: Introductionmentioning
confidence: 99%
“…Some reported metal complexes of chalcones also exhibit antihyperglycemic and antimicrobial activities [29,30] . The electrochemical properties of various chalcones have been demonstrated using a three‐electrode cell system in the presence of anhydrous acetonitrile and tetrabutylammonium hexafluorophosphate electrolyte [31–33] . In addition, Slobodinyuk et al reported the electrochemical oxidation of series of asymmetric chalcones [34] .…”
Section: Introductionmentioning
confidence: 99%